2020
DOI: 10.1155/2020/9357426
|View full text |Cite
|
Sign up to set email alerts
|

Is International Travel an Emerging Issue on Transmission of Beijing Lineage Mycobacterium tuberculosis?

Abstract: Mycobacterium tuberculosis belonging to Beijing sublineage (BL) is associated with high tuberculosis (TB) transmission, multidrug resistance, and adverse treatment outcomes. Sri Lanka experiences an increase in the number of travellers/workers to and from high TB-burden countries, and there is risk of getting BL strains imported into the country. In this context, a cohort study was conducted to assess the prevalence of BL strains among pulmonary tuberculosis (PTB) patients in the Kandy district of Sri Lanka (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(36 reference statements)
0
1
1
Order By: Relevance
“…We found that the L2 lineage had a high percentage of retreated cases, consistent with previous reports that showed this lineage to have a higher relapse rate and an association with drug resistance [ 9 , 28 , 29 ]. However, our finding of higher sputum grading in L1 lineage was not consistent with the finding of no association in South Africa study and higher grading of L2 in Sri Lanka study [ 30 , 31 ].…”
Section: Discussioncontrasting
confidence: 99%
“…We found that the L2 lineage had a high percentage of retreated cases, consistent with previous reports that showed this lineage to have a higher relapse rate and an association with drug resistance [ 9 , 28 , 29 ]. However, our finding of higher sputum grading in L1 lineage was not consistent with the finding of no association in South Africa study and higher grading of L2 in Sri Lanka study [ 30 , 31 ].…”
Section: Discussioncontrasting
confidence: 99%
“…It is also important for those countries that have low TB burden but have a great influx of immigrants. There is a need to monitor the kinetics and trends of MTB lineages especially Beijing lineage and others that have well-documented drug resistance in order to devise appropriate actions to combat the associated risks [ 55 ].…”
Section: Genetic Aspects Of Tbmentioning
confidence: 99%